Evolution of Carbonate‐Intercalated γ‐NiOOH from a Molecularly Derived Nickel Sulfide (Pre)Catalyst for Efficient Water and Selective Organic Oxidation. Issue 16 (18th January 2023) - Ghosh, Suptish; Dasgupta, Basundhara; Kalra, Shweta; Ashton, Marten L. P.; Yang, Ruotao; Kueppers, Christopher J.; Gok, Sena; Alonso, Eduardo Garcia; Schmidt, Johannes; Laun, Konstantin; Zebger, Ingo; Walter, Carsten; et al.
Abstract: The development of a competent (pre)catalyst for the oxygen evolution reaction (OER) to produce green hydrogen is critical for a carbon‐neutral economy. In this aspect, the low‐temperature, single‐source precursor (SSP) method allows the formation of highly efficient OER electrocatalysts, with better control over their structural and electronic properties. Herein, a transition metal (TM) based chalcogenide material, nickel sulfide (NiS), is prepared from a novel molecular complex [Ni II (PyHS)4 ][OTf]2 (1 ) and utilized as a (pre)catalyst for OER. The NiS (pre)catalyst requires an overpotential of only 255 mV to reach the benchmark current density of 10 mA cm −2 and shows 63 h of chronopotentiometry (CP) stability along with over 95% Faradaic efficiency in 1 m KOH. Several ex situ measurements and quasi in situ Raman spectroscopy uncover that NiS irreversibly transformed to a carbonate‐intercalated γ−NiOOH phase under the alkaline OER conditions, which serves as the actual active structure for the OER. Additionally, this in situ formed active phase successfully catalyzes the selective oxidation of alcohol, aldehyde, and amine‐based organic substrates to value‐added chemicals, with high efficiencies. Abstract : A single‐source precursor‐derived NiS (pre)catalyst (NiS‐M) is developed for the oxygen evolution reaction (OER). Under oxidation potential, it transforms in situ into a CO3 2− ‐intercalated γ−NiOOH active phase and shows superior OER activity. Additionally, the NiS‐M (pre)catalyst also successfully catalyzes the selective oxidation of small organic molecules to value‐added chemicals.